Electrokinetics In Nanocomposites: Nanoparticle Reshaping and Ion Migration in Nanocomposite Ultrafast Ionic Actuators: The Converse Piezo–Electro–Kinetic Effect (Adv. Funct. Mater. 31/2019). (29th July 2019) - Chiolerio, Alessandro; Perrone, Denis; Roppolo, Ignazio; Rizza, Giancarlo; Risplendi, Francesca; Stassi, Stefano; Laurenti, Marco; Rajan, Krishna; Chiappone, Annalisa; Bocchini, Sergio; Cicero, Giancarlo; Pandolfi, Paolo; et al.
Abstract : In article number1902941, Alessandro Chiolerio and co‐workers describe, the converse piezo‐electro‐kinetic (CPEK) effect, which is a nonequilibrium electric‐field‐driven surface atom drift able to introduce structural anisotropy on former spherical metallic nanoparticles, resulting in an elongation of the whole nanocomposite hundred‐fold times the electrostriction effect.